Do preferential trade agreements increase their members' foreign direct investment? - Max Büge (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
The mushrooming of preferential trade agreements (PTAs) has represented a puzzle in international economics and international relations since the mid-1990s. A possible explanation is that PTAs are not so much about trade per se, but that PTAs are a strategic instrument in the international competition for foreign direct investment (FDI). The objective of this paper is to test for the hypothesis that a PTA increases bilateral FDI. The estimator builds upon recent theoretical work on the determinants for FDI that – similar to gravity models in international trade – takes multilateral resistance into account. Since PTA formation is not an exogenous predictor variable, I apply estimation techniques that are borrowed from microeconometrics in order to control for endogeneity. I find that a PTA has a strong and robust average treatment effect on FDI (for developed and developing countries). Furthermore, I control for the average treatment effect of bilateral investment treaties (BITs) and find a clear pattern: BITs between a developed and a developing country increase FDI from the former to the latter, controlling for reverse causality. By contrast, the econometric results suggest no robust average treatment effect of BITs between developed countries on their bilateral FDI. But it appears that pairs of high income countries with high levels of FDI in the first place are less likely to conclude BITs.
Keywords: 330; Handel und Investitionen; Regionale + globale + transnationale Governance